257 HIGH TEMPORAL RESOLUTION BREATH-HOLD CINE MAGNETIC RESONANCE IMAGING CORRELATES WITH TISSUE DOPPLER IMAGING IN REVEALING VENTRICULAR DSSYNCHRONY IN HEART FAILURE. (1st January 2006) - Alvergue, J.; Dinh, H. V.; Fonseca, C.; Child, J.; Valderrabano, M.; Shivkumar, K.; Fonarow, G. C.; Finn, J. P.
Abstract : Purpose: Cardiac resynchronization therapy (CRT) improves symptoms in heart failure (HF) patients with ventricular dyssynchrony. At present, tissue Doppler imaging (TDI) can assess differences in contraction times between regions of the left ventricle and may predict which patients will response to CRT. Conventional MRI sequences are inadequate to detect such subtle differences. High temporal resolution (HTR), on the order of 200 Hz, is required. In this study, we compare segmental cardiac contraction parameters in HF and controls using a novel MRI sequence with such resolution. Methods: Eleven healthy volunteers and six patients with NYHA class III-IV HF (2 non-ischemic, 4 ischemic, QRS 122 ± 42) were scanned using a high temporal resolution TRUFISP cine sequence (TR/TE 5.1/1.1 ms; FA 58; FOV 236*360 mm; matrix 92*192; slice thickness 7 mm, bandwidth 964 Hz/pixel) on a 1.5 T MR system (Siemen's Avanto). Images were analyzed on post-processing software platforms, Siemen's Medical Solution. Time from onset of QRS (trigger) to minimal regional endocardial volume and maximal wall thickness (peak regional contraction [Tp]) was determined for all the standard 16-segment cardiac regions. Echo TDI for HF were also compared to MRI parameters. Results: There was significant differences in the Tp times between HF and controls (delta Tp) in the mid inferior and mid infero-lateral segments (70 ms ± 78 ms for HF vs 3.0 ms + 11 ms for normals, p = .01), as well as mid anterior and mid antero-lateral segments (62.0 ms ± 105 ms for HF vs -4.0 ms ± 9.7 ms for normals, p = .05) (Table). Furthermore, positive correlation coefficients were obtained when dyssynchrony indices in the basal postero-septal and basal infero-lateral segments (corr = 0.53), as well as basal antero-septal and basal infero-lateral segments (corr = 0.91) obtained by MRI were compared to TDI derived values. Conclusions: HF patients have significant regional contraction delays and dyssynchrony, which can be detected by HTR breath-hold cine MRI with good correlation to values as measured by TDI. Larger trials are on going to confirm our findings.